2021
DOI: 10.1177/0020764021997479
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, contact and stigma of mental illness: Comparing three stakeholder groups in Hong Kong

Abstract: Background: It remains unknown what the impacts of multiple dimensions of contact (e.g. level, quantity and quality) are on the stigma of mental illness. Aims: To explore the relationship between the multiple dimensions of contact and stigma of mental illness among family members (FM), mental health workers (MHW) and community residents (CR) in Hong Kong. Methods: The stigma, contact and knowledge were measured in FM, MHW and CR in Hong Kong. Multiple regression analyses were used. Results: MHW ( n = 141) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 51 publications
11
34
1
Order By: Relevance
“…The negative correlation between public stigma towards people with COVID-19 and knowledge, as shown in this study, has been repeatedly verified in other similar stigmatizing conditions, including infectious disease and mental disorders [ 41 , 42 ]. The findings of this study suggested that misconceptions of COVID-19 were correlated with stigmatizing notions.…”
Section: Discussionsupporting
confidence: 77%
“…The negative correlation between public stigma towards people with COVID-19 and knowledge, as shown in this study, has been repeatedly verified in other similar stigmatizing conditions, including infectious disease and mental disorders [ 41 , 42 ]. The findings of this study suggested that misconceptions of COVID-19 were correlated with stigmatizing notions.…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, this is the first randomized controlled trial in rural China to examine the effectiveness of the ECM intervention on reducing the affiliate stigma of FCPWS. Given the negative contact may increase stigma, 18 the ECM intervention, a new intervention model, emphasizes positive contact with persons with schizophrenia. Allport's theory specified contact at equal power levels for stigma change to occur, 13 but this type of contact with persons with schizophrenia may be even less likely to occur in rural China given the lack of peer supports and the limited treatment (e.g., antipsychotic medication) for persons with schizophrenia in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although community mental health care has been developed in current China, over 90% of persons with schizophrenia are cared for by their family caregivers at home in rural areas. 15 , 16 , 18 Given the limited community mental health services and the important role of family caregivers in caring for persons with schizophrenia in China, effective anti-stigma interventions for these caregivers need to be developed. This study tested the effectiveness of the ECM intervention, a new anti-stigma model, on reducing affiliate stigma of FCPWS which contributes to the contact theory by emphasizing the specific role of positive contact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations